VALIDITAS ISI POSTER DIGITAL AUDIOVISUAL UNTUK PENCEGAHAN PERUNDUNGAN VERBAL DI SEKOLAH DASAR - Febriani, Githa; Miranda, Dian; Irfan Izudin, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the content validity of an audiovisual digital poster as a medium for preventing verbal bullying in elementary schools. The poster is organized into three phases: Phase A for Grade I–II students, Phase B for Grade III–IV students, and Phase C for Grade V–VI students. The study employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, and development. The research focused on testing the content validity of the poster. The validation process involved four validators consisting of two material experts and two design experts. The results of material validation showed Aiken’s V values of 0.97368 for Phase A, 0.98246 for Phase B, and 0.92982 for Phase C, all of which fall into the “very valid” category. The design validation results showed Aiken’s V values of 0.93056 for Phase A, 0.94444 for Phase B, and 0.95833 for Phase C, which are also categorized as “very valid”. Based on these results, it can be concluded that the audiovisual digital poster has a very high level of content validity in terms of both material and design aspects, making it highly suitable for product trials.